Pelatihan Detector Kebocoran Liquid Petroleum Gas (LPG) Sebagai Media Belajar Teknologi - Hadi, Sirojul; Dewi, Puspita; Soraya, Siti; Yasa, I Nyoman Miyarta; Yunika, Regina Pricilia (Insan Kreasi Media, 2022)
Fires in homes can be caused by short circuits and leakage of Liquid Petroleum Gas (LPG). LPG gas leaks are very dangerous because apart from being able to cause fires, they can also cause explosions so LPG leaks need to be dealt with quickly so as not to cause greater damage. One way to overcome this is by training the community to make LPG gas detectors. The result of the PKM is that effective training can be carried out for junior high school children, senior high schools, and the general public.